Culinary linguistics : the chef's special - Gerhardt, Cornelia; Frobenius, Maximiliane; Hucklenbroich-Ley, Susanne (Culture and language use ;, 2013)
There is a relative dearth of taste words in English, in contrast to words for other senses. We argue that this does not reflect an accompanying lack of knowledge about taste or an inability to perceive tastes. Taste knowledge was explored in an object description task and a rating task in an experimental setting and showed that whilst participants knew a lot about taste, they used few words to describe it. A search of taste words in a public corpus showed that taste words are often derivative from a source noun, refer to components, and that they are also ambiguous and polysemous.